Preparo para alta hospitalar do paciente cirúrgico/acompanhante: validação de tecnologia cuidativo-educacional - Colussi, Giovana (2021)
Upon hospital admission of the patient, planning for hospital discharge should be initiated in order to promote a safe and effective transition of care, avoiding readmissions and ensuring continuity of care at home. The incorporation of technologies in the perioperative period can help professionals to carry out educational and care actions aimed at the patient and companion, involving them in a dialogical system and encouraging individual and collective autonomy. The use of a guide aimed at preparing the surgical patient / companion for hospital discharge can serve as a mediating tool in the care-educational process experienced by the health professional, the patient and their companion. This study had as general objective to validate a preparation guide for a hospital discharge of the surgical patient / companion to make it a Care-Educational Technology (TCE). Methodology: this is a methodological research on content validation. Twenty-two expert judges participated in the study, namely: 12 nurses, eight physiotherapists and two nutritionists. These were selected according to the inclusion criteria selected with convenience sampling in association with the Snowball model. Invited guests to participate in the study via email. Data collection took place through an instrument read by the researcher according to a five-point Likert scale. An analysis of quantitatively captured data using the Content Validity Index (CVI) for the evaluative item contained in the instrument domains and the calculation of the global CVI. Ethical aspects were respected in accordance with Resolution 466/2012. Results: according to the experts, the guide has inferior content both to the professional and the surgical patient / companion, in addition to being easy to handle and read. The suggestions made covered issues about language, text objectivity, use of fewer technical terms, step-by-step description of procedures, modification and inclusion of images for greater clarity, as well as the inclusion of links to videos and selected sites for consultation, reorganization and updating of references and inclusion of useful telephone numbers. The global CVI reached a score of 0.83, higher than that established, therefore, the expert judges considered the guide a statistically valid TBI. The (re)adjustments of the guide were carried out in order to improve it to increase its credibility and veracity of information. Conclusion: the guide is a TBI that can help health professionals to plan hospital discharge for a transition from home care with reliable and necessary guidance to contribute to good home rehabilitation. It is estimated that a TBI contributes to the development of autonomy and empowerment of the surgical patient / companion in terms of self-care and in contributing to the construction of knowledge in nursing.